Design and Construction of Door Security System using Radio Frequency Identification based on The Internet of Things at The Main Power House Warehouse of Juanda Airport Surabaya - Solikin, Akhmad; Wildan Surya Wijaya (Universitas PGRI Adi Buana Surabaya, 2024)
In an increasingly advanced world, people have valuable documents and personal items such as cell phones, laptops, power banks, especially for people who work in office areas because they really need these valuable items for work purposes. However, there are several things that become problems when bringing these valuable items to the office where the office still uses manual door locks.